Comparison of Letrozole and Clomiphene in Infertile Male Patients with Oligoasthenozoospermia: Comparison of Letrozole and Clomiphene in Male Infertility - Seerwan, Muhammad; Ilyas, Muhammad; Adnan, Muhammad; Muzammil, Muhammad; Saifullah, .; Durrani, Ali Shandar (Pakistan Journal of Health Sciences, 2025)
Infertility often causes significant emotional distress, and in about 50% of cases, male factors such as oligoasthenozoospermia play a key role in the challenges you’re facing. Objectives: To compare two medications, clomiphene citrate and letrozole, to see which one works better for improving sperm count and motility in men with oligoasthenozoospermia. Methods: This non-randomized controlled study was conducted at DHQ Teaching Hospital in D.I. Khan with 140 men diagnosed with oligoasthenozoospermia. Participants were divided into two groups of 70, receiving either letrozole or clomiphene citrate. Sperm concentration and motility were measured at three months, with improvements compared between the two groups. Statistical analysis was performed using SPSS version 21, with p-values <0.05 considered significant. Results: Both letrozole and clomiphene significantly improved sperm concentration and motility, with letrozole showing greater improvement in both parameters compared to clomiphene citrate. An increase of 48.23% in sperm concentration was observed in the letrozole group, while the clomiphene citrate group showed a 26.26% increase at 12 weeks post-treatment. Sperm motility improved by 42.08% with letrozole and by 18.55% with clomiphene citrate at the 12-week mark. Conclusions: Both letrozole and clomiphene citrate have been shown to improve sperm parameters in men diagnosed with oligoasthenozoospermia. The letrozole group showed a more significant effect than the clomiphene group.